Brownovo gibanje z elastičnimi trki - Likar, Andrej (Obzornik za matematiko in fiziko, 2021)
Famous Brownian motion, which gives physics a lot of important clues, is treated with elastic collisions between spherical particles of the medium and those with the massive Brownian particle. For energy dissipation we do not need Stokes force on spherical particle in viscous medium, which is valid only for uniform motion and sizes of particles where hydrodynamic equations are valid.
Keywords: Brownovo gibanje